Cross-Sectional Examination of Musculoskeletal Pain and Physical Function in a Racially and Socioeconomically Diverse Sample of Adults. (3rd October 2020) - Sardina, Angie L; Gamaldo, Alyssa A; Andel, Ross; Johnson, Shanthi; Baker, Tamara A; Thorpe, Roland J; McEvoy, Cathy; Evans, Michele K; Zonderman, Alan B
Abstract: Background: Musculoskeletal pain alters physiological function, which may be evidenced as early as middle age. Previous research has concluded that middle-aged adults are a high-risk group for musculoskeletal pain and report functional limitations similar to older adults. However, few studies have examined the relationships between musculoskeletal pain and physical function, using objective performance measures in a sample of racially and socioeconomically diverse adults. Thus, this study examined musculoskeletal pain in relation to physical function in middle-aged (30–64 years) White and Black adults and investigated whether the relationship varied by sociodemographic characteristics. Methods: This cross-sectional examination incorporated data from the Healthy Aging in Neighborhoods of Diversity across the Life-Span Study. Participants ( n = 875) completed measures of musculoskeletal pain and objective measures of physical performance (ie, lower and upper body strength, balance, and gait abnormalities). Physical performance measures were standardized to derive a global measure of physical function as the dependent variable. Results: Approximately, 59% of participants identified at least 1 pain sites ( n = 518). Multivariable regression analyses identified significant relationships between greater musculoskeletal pain and poorer physical function (β = −0.07, p = .031), in mid midlife (β = −0.04, p = .041; age 40–54) and late midlife (β = −0.05, p = .027; age 55–64). Conclusions: This study observed that musculoskeletal pain was associated with poorer physical function within a diverse group of middle-aged adults. Future research should longitudinally explore whether chronic musculoskeletal pain identified at younger ages is associated with greater risk for functional limitation and dependence in later life.